2021
DOI: 10.1292/jvms.20-0498
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine elevation in the mouse small intestine at the early stage of infection with the gastrointestinal parasite <i>Heligmosomoides polygyrus</i>

Abstract: To eliminate pathogens, the initiation of an appropriate immune response is critical. When the gastrointestinal nematode, Heligmosomoides polygyrus (Hp), invades the small intestine, a type-2 cytokine response is initiated; however, this response is not sufficient to clear the infection, and chronic infection can ensue. In this study, the host defense against Hp was investigated in mice with a focus on the role of CD4+ T cells. To this end, tissues from the small intestine and mesenteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Tissue-dwelling nematodes, on the other hand, follow different survival strategies. For instance, H. polygyrus penetrates the epithelium and submucosa of the small intestine before embedding in the smooth muscle tissue and returning to the lumen around 8 dpi (69). Although anti-parasite responses are formed early after infection, peaks of type 2 cytokines are observed at day 8 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-dwelling nematodes, on the other hand, follow different survival strategies. For instance, H. polygyrus penetrates the epithelium and submucosa of the small intestine before embedding in the smooth muscle tissue and returning to the lumen around 8 dpi (69). Although anti-parasite responses are formed early after infection, peaks of type 2 cytokines are observed at day 8 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that excessive production of cytokines contributes to the pathophysiology of a range of diseases [22]. During infection, the rapid initiation of an appropriate immune response and the induction of specific immune cells and molecules is important for the elimination of pathogens [23]. It has been reported earlier that the expressions of pro-inflammatory cytokines, mainly IL-1β, IL-6, and TNF-α, in the intestinal mucosa of IBD patients were found to be markedly enhanced [24].…”
Section: Discussionmentioning
confidence: 99%
“…The host innate immune response is the body’s first line of defense against pathogens [ 1 , 2 ]. Human innate immune receptors recognize conserved signatures on pathogens known as pathogen associated molecular patterns (PAMPs), which are important signaling molecules released by pathogens during infection [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%